Transformasi Organisasi Islam di Era Digital - Manurung, Marzuki; Doloksaribu, Thorino Ivan; Widad, Mahdy Husnul (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
The advancement of digital technology has significantly impacted various aspects of life, including Islamic organizations. Digital transformation requires these organizations to adapt in terms of management, communication, and da'wah dissemination to remain relevant in the modern era. This study aims to analyze how Islamic organizations utilize digital technology to expand their reach, enhance program effectiveness, and address challenges such as misinformation and shifting societal interaction patterns. The research employs a literature review and case study analysis of several Islamic organizations that have adopted digital platforms. The findings indicate that digital transformation offers significant opportunities to strengthen membership networks, streamline coordination, and improve transparency. However, a strategic approach is needed to maintain a balance between Islamic values and technological dynamics. This study is expected to serve as a reference for Islamic organizations in designing effective and sustainable digital transformation strategies.